Evaluating Recruitment among Female Sex Workers and Injecting Drug Users at Risk for HIV Using Respondent-driven Sampling in Estonia - Uusküla, Anneli (Springer US, 2010)
Few recent publications have highlighted theoretical and methodological challenges using respondent-driven sampling (RDS). To explore why recruitment with RDS may work in some populations and not in others, we assess the implementation of RDS to recruit female sex workers (FSWs) and injection drug users (IDUs) into a human immunodeficiency virus biological and risk behavior survey in Tallinn, Estonia. Recruitment of FSWs was slower and more challenging than that of IDUs. The IDU study recruited 350 participants within 7 weeks, while the FSW study recruited 227 participants over 28 weeks. Implementation modifications that did not negatively impact key RDS theoretical and methodological requirements were used to improve recruitment during the FSW study. We recommend that all RDS studies include a formative research process to involve the participation of target populations and key persons associated with these populations in the study planning and throughout the implementation processes to improve recruitment from the outset and to respond to poor recruitment during data collection.